Energy and matter fluxes of a spruce forest ecosystem - Foken, Thomas (Springer, 2017)
This book focuses on fluxes of energy, carbon dioxide and matter in and above a Central European spruce forest. The transition from a forest affected by acid rain into a heterogeneous forest occurred as a result of wind throw, bark beetles and climate change. Scientific results obtained over the last 20 years at the FLUXNET site DE-Bay (Waldstein-Weidenbrunnen) are shown together with methods developed at the site, including the application of footprint models for data-quality analysis, the coupling between the trunk space and the atmosphere, the importance of the Damköhler number for trace gas studies, and the turbulent conditions at a forest edge. In addition to the many experimental studies, the book also applies model studies such as higher-order closure models, Large-Eddy Simulations, and runoff models for the catchment and compares them with the experimental data. Moreover, by highlighting processes in the atmosphere it offers insights into the functioning of the ecosystem as a whole. It is of interest to ecologists, micrometeorologists and ecosystem modelers.
Keywords: Forest ecology -- Europe, Central.; Spruce -- Europe, Central.; Central Europe.; elektronické knihy; electronic books